Analysis of Islamic Law on Consumer Protection in Hajj and Umrah Business in Indonesia - Palangkey, Rahmi Dewanty; Gassing, A Qadir; Salenda, Kasjim; Marilang,, Marilang; Syamsu Rijal, Tabhan (Universitas Islam Negeri Raden Intan Lampung, 2021)
This research is motivated by the failure of thousands of Umrah pilgrims to go to Mecca since 2017 but do not get their rights as consumers. Several facts prove that although regulations related to Hajj and Umrah organizers as well as the Consumer Protection Act have explicitly regulated consumer rights, in reality the pilgrims who are victims of hajj and umrah travel agency fraud are still not getting consumer protection. This research is a descriptive qualitative research using a normative juridical approach. Sources of data used in this study are primary data and secondary data obtained from interviews and document studies. This study concludes that the presence of Law No. 8 of 2019 concerning the Implementation of Hajj and Umrah contains the spirit of upholding consumer protection in the Hajj and Umrah business. However, its success is largely determined by the extent to which the regulator empowers internal supervisors to prevent irresponsible practices of hajj and umrah travel agencies. On this side, unfortunately, the role of guidance, supervision and legal protection carried out by the Indonesian Ministry of Religion as a regulator in protecting Hajj and Umrah pilgrims seems to be still at a very low level.